The Association Between Serum Thyrotropin Within the Reference Range and Metabolic Syndrome in a Community-Based Chinese Population - Li M (Dove Medical Press, 2020)
Meng Li,1,* Xiuying Zhang,1,* Xianghai Zhou,1 Xueyao Han,1 Rui Zhang,1 Zuodi Fu,2 Lianying Wang,2 Ying Gao,1 Yufeng Li,2 Linong Ji1 1Department of Endocrinology and Metabolism, Peking University People’s Hospital, Peking University Diabetes Center, Beijing, People’s Republic of China; 2Department of Endocrinology and Metabolism, Capital Medical University Pinggu Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linong JiDepartment of Endocrinology and Metabolism, Peking University People’s Hospital, Beijing 100044, People’s Republic of ChinaTel/Fax +86-10-88324371Email jiln@bjmu.edu.cnYufeng LiDepartment of Endocrinology and Metabolism, Capital Medical University Pinggu Hospital, Beijing 101200, People’s Republic of ChinaTel/Fax +86-10-89978790Email doctorlyf@126.comPurpose: We aimed to ascertain the association between thyrotropin (TSH) levels in euthyroid state and the prevalence of metabolic syndrome (MetS) in a community-based Chinese population.Participants and Methods: Based on a large and well-characterized community cohort in Beijing, China, 1831 men and 1742 women with serum TSH levels within the reference range (0.50– 4.78 μIU/mL) were stratified by quartiles of TSH (Q1-4). MetS was identified according to the criteria of International Diabetes Federation guidelines. Poisson regression models were used to estimate the association between serum TSH and the prevalence of MetS and its components before and after adjustment for potential confounding factors. The reported association was measured using the prevalence ratio (PR) with its respective 95% confidence interval (95% CI).Results: The prevalence of MetS in euthyroid population across TSH quartiles (Q1-4) was 38.9%, 44.6%, 41.0%, and 47.7%, respectively, in men (P = 0.045), and 47.7%, 46.6%, 46.9%, and 54.6%, respectively, in women (P = 0.032). Compared with the reference group TSH-Q1, the prevalence of MetS was higher among TSH-Q4 group both in men (PR = 1.27; 95% CI: 1.09, 1.48, P = 0.002) and women (PR = 1.21; 95% CI: 1.07, 1.37, P = 0.003) even after adjustment for age, lifestyle factors, serum levels of free triiodothyronine (FT3), and free thyroxine (FT4). Most of the components of MetS were common in higher serum TSH levels within the normal range.Conclusion: The prevalence of MetS and most of its components increased in the higher TSH group in euthyroid Chinese population.Keywords: thyroid hormones, obesity, hypertension, hyperglycemia